The Art of C : elegant programming solutions - Schildt, Herbert (Berkeley, California : Osborne McGraw-Hill, 1991)
This is a guide to C which gives instructions for high-level programming. A significant revision of C: power user's guide , this book/disk (5.25) package combines theory, background, and code; provides 28 programs; and includes interviews with world-class C programmers. Compatible with virtually all DOS-based C compilers. Annotation copyright Book News, Inc. Portland, Or.
Preface -- One. Pop-up and Pull-down Menus -- Two. Pop-up Windows -- Three. TSR Pop-up Programs -- Four. Graphics -- Five. Video Games -- Six. Using the Serial Port: File Transfers and a Poor MAN's LAN -- Seven. Language Interpreters -- Eight. Of Screens and Speakers -- Nine. Interfacing to the Mouse -- Ten. Creating Business Bar Graphs -- Index.
Includes bibliographical references and index.
Keywords: C (PROGRAMMING LANGUAGE)